(untitled) (Journal of Information Technologies in Education (ITE), 2007)
We analyze general prerequisites and trends for change in the process of teaching in secondary and high education on the modern stage of society development. These trends determine corresponding changes in the system of methods of teaching and pedagogical technologies.